Exploring the Suitability of Blockchain Technology in Improving Inter-Organizational Collaboration Workflows in E-Payment Processes at the Transport License Department of Malaysia - Naharudin Saadan; Khairil Faizal Khairi (AMH International Conferences and Seminars Organizing LLC, 2025)
Indexed